(untitled) (London Journal of Research In Management & Business, 2024)
The intersection between institutional evaluation and strategy is an underexplored field in scientific literature, characterized by the lack of studies deeply investigating this relationship. This article aims to fill this gap, identifying the critical variables that restrict the participation of the Self-Assessment Commissions (CPAs) in the strategic anticipation process in higher education institutions. The literature review covers the main authors who discuss the practice of foresight and those who analyze the relationship between evaluation and strategic planning in academic environments. Using a mixed-methods approach, focusing on descriptive statistics and the coding proposed by Grounded Theory, this study highlights the lack of incentive for the strategic participation of CPAs - the main quality assurance in Brazilian higher education - on the part of the investigated institutions. The conclusions highlight theoretical and practical contributions, especially by pointing out the critical conditions that can be used by institutions to improve the strategic training.